A hierarchical logistic regression predicting rapid respiratory rates from post-exertional malaise. Issue 4 (1st October 2020) - Cotler, Joseph; Katz, Ben Z.; Reurts-Post, Corine; Vermeulen, Ruud; Jason, Leonard A.
ABSTRACT: Background: Past research has found high rates of hyperventilation in patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), but hyperventilation can be influenced by psychological factors. Clinical respiratory rates have been less frequently assessed. Aim: This study aimed to identify the predictors of rapid respiratory rates in patients referred an outpatient clinic specializing in ME/CFS. Methods: Adults ( n  = 216) referred to an outpatient clinic specializing in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) participated in a two-day cardiopulmonary exercise test. As part of that evaluation, subjects had resting respiratory rates measured on two consecutive days. The current study used questionnaires to assess the relationship between tachypnea (rapid respiratory rates) and a variety of domains including post-exertional malaise (PEM), a common complaint in patients with ME/CFS, and psychiatric/somatic symptoms, using hierarchical logistic regression analysis. Results: PEM was a significant predictor of tachypnea, while psychological/somatic assessments and sedentary behaviors were not significantly predictive of tachypnea. Conclusions: These findings suggest that respiratory rate may be useful as an objective clinical metric of PEM, and potentially ME/CFS.